Occupational pensions and interfirm job mobility in the European Union. Evidence from the ECHP survey - Vincenzo Andrietti (University of Essex, Institute for Social and Economic Research (ISER), 2000)
Discussion of problems posed by defined benefit occupational pension plans to the free circulation of private sector workers in the European Union has been mainly driven by the theoretical arguments, while little attempt has been made to support these arguments with empircal evidence. The papers main objective is to fill this gap, modelling the role of expected pension portability losses on individual job mobility choices in a sample of European Union Member States with different pension portability rules, and estimating the model with a new longitudinal data set derived from the first two waves of the European Community Household Panel survey. Individual job mobility status is seen as endogenously determined through a comparative evaluation of expected benefits and costs from mobility. Following Heckmans (1979) two-step procedure, we consistently estimate wage equations parameters and individual mover/stayer structural wage differentials corrected for self-selectivity. Maximum likelihood estimatation of a structural probit equation accounting for estimated wage differentials allows the recovering of structural mobility costs parameters. In particular, occupational defined benefit pensions seem to act, through pension portability losses, as a significant impediment to individual labour mobility in all countries but Spain, while evidence for Denmark is consistent with full portability of defined contribution pensions.
Keywords: 330